PENGARUH PAJANAN PARTICULATE MATTER 10 (PM10) DI UDARA TERHADAP KELUHAN SISTEM PERNAPASAN MASYARAKAT DI SEKITAR PABRIK SEMEN X DESA TIPAR KIDUL KECAMATAN AJIBARANG TAHUN 2018 - Jati Firmanto; Mela Firdaust; Hikmandari Hikmandari (Poltekkes Kemenkes Semarang, 2019)
Background Industrial activity important for economic growth but also adversely affects health such as PM10 particulate emissions. Environmental Protection Agency in the World Bank, estimates that 90% of air-fired PM10 contains sulfur dioxide (SO2). From the results of several studies known dust particles (PM10) can cause inflammation of the airways and can trigger the occurrence of asthma (Darmono, 2010 and ATSDR, 2011). The purpose of this study was to analyze the effect of PM10 exposure in air to respiratory system complaints. This type of research uses observational analytics. The method used is cross sectional. The sample in this study were 32 respondents exposed group and 32 respondents group not exposed. The results showed that the mean intake of PM10 was 0.16663 mg / kg / day in the exposed group and 0.04252 in the unexposed group. While percentage of respondents who have respiratory system complaints that is as much as 65.6% in the exposed group and 34.4% in the group not exposed. It is conclude based on the result of multiple logistic regression test that is variables that influence the respiratory system complaints yatu intake PM 10 with p value equal to 0,048 and history of respiratory disease with p value 0,039 (p value 0,05). Suggestion from the results of this study is expected to make some efforts to prevent particulate entry into the home and the government is expected to monitor the quality of the environment on a regular basis as material consideration of the extension of industrial permit.